Impact of the COVID-19 Pandemic on Lactation Room Implementation: Intersection of Public Policy and Health Crisis in Peru - Nuñez-Herrera, Rebeca Mercedes (2024)
Objective: To assess the behavior of the implementation of institutional lactators following the COVID-19 pandemic in Peru since 2016 to 2022. Material and Method: It was a quasi-experimental design study with a sample of 3,254 institutional lactators, records were taken from the annual reports published by the MIMP from 2016 -2022. An interrupted time series analysis was applied to analyze the change in trend of lactation implementation during the pandemic. Results: There was a significant change in the implementation of breastfeeding during the pandemic stage. Before the arrival of the pandemic, the trends observed in the time series were analyzed. It maintained an average of significant increase of 189 lactations each year. This trend provided a baseline to evaluate changes due to the pandemic interruption. After the start of the pandemic in 2020, an immediate change was observed in the implementation of breastfeeding, it decreased by 589 breastfeeding, being statistically significant according to the analysis carried out. Conclusions: A constant increase was observed per year, but the arrival of the pandemic caused a temporary decrease that was recovered in the post-pandemic period.